2003
DOI: 10.1046/j.1341-8076.2003.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective sexuality and female circumcision: The cause and the possible management

Abstract: Counseling parents about these sexual defects and asserting the need for correcting the mutilation, which resulted from these circumcisions, are effective steps in banning such procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
98
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 9 publications
14
98
0
5
Order By: Relevance
“…34 A more elaborate hospital-based study in Egypt, published in 2003, found that women with Type I FGM/C experienced no reduction in sexual desire, while those who had undergone Type II or III experienced several sorts of sexual problems. 35 These findings are in line with a review in the same year that found that dyspareunia (painful intercourse) was experienced by 16-46% of the women with FGM/C compared to 14-32% of the women without it. 36 In 2007, a survey of 1,000 married women in Egypt, of whom more than 90% were circumcised, found that almost 70% of circumcised women experienced some sort of sexual dysfunction.…”
Section: Relationship Between Female Genital Mutilation/cutting and Ssupporting
confidence: 87%
See 2 more Smart Citations
“…34 A more elaborate hospital-based study in Egypt, published in 2003, found that women with Type I FGM/C experienced no reduction in sexual desire, while those who had undergone Type II or III experienced several sorts of sexual problems. 35 These findings are in line with a review in the same year that found that dyspareunia (painful intercourse) was experienced by 16-46% of the women with FGM/C compared to 14-32% of the women without it. 36 In 2007, a survey of 1,000 married women in Egypt, of whom more than 90% were circumcised, found that almost 70% of circumcised women experienced some sort of sexual dysfunction.…”
Section: Relationship Between Female Genital Mutilation/cutting and Ssupporting
confidence: 87%
“…We have followed the path of many anthropologists, in that context is considered the main parameter for the construction of sexuality. [18][19][20] The existing literature on FGM/C and sexuality, published from 1965 until today, mostly since the early 1990s, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] is conflicting regarding the effects of FGM/C on sexual feelings. Several socioanthropological studies over the past 20 years have challenged what they call the "western assumption"* that the clitoris is key to female sexual response, and that FGM/C has a negative effect on sexual feelings.…”
Section: Relationship Between Female Genital Mutilation/cutting and Smentioning
confidence: 99%
See 1 more Smart Citation
“…22 In Egypt, Thabet concluded that type I female genital cutting did not affect women's sexual desire. 23 Desire, arousal, orgasm, satisfaction and pain scores did not show considerable differences between circumcised and uncircumcised women in a hospital-based study on Egyptian women or in a recent study over 150 overweight and obese women from Upper Egypt. 5,24 Though statistically insignificant, lower educational level in our study was associated with FSD.…”
Section: Discussionmentioning
confidence: 70%
“…Statistically signifi cant diffi culties were found in circumcised women to include a lack of sexual desire, less initiation of sexual activity with husbands and being less likely to experience climax (see also Khaled and Vause, 1996;Thabet and Thabet, 2001). Research has also indicated that when the clitoris is destroyed by FGM/C women compensate by 'shifting' this once most sensitive part of their bodies and instead identify their breasts as the most sensitive area (Nwajei and Otiono, 2003).…”
Section: Psychological and Sexual Health Implicationsmentioning
confidence: 99%